How to borrow and repay business loans : A practical guide to mastering the secrets of borrowing (and repaying) business loans successfully and efficiently - Echezona, Chukwunwike (Enugu: Silver and Gold Ent. Ltd, 1992)
The book is based on inside knowledge, practical experience and a burning desire to improve the borrowing efficiency of the nation's private sector.
rpm 05/09/16, ijb 14/03/2019
Loans
Keywords: Business loans; Borrowing; Repaying loans; Nigerian Banks; Nigeria